Substitution of human for horse urine disproves an accusation of doping - Diaz, Silvina (2008)
In order to detect switching and/or manipulation of samples, the owner of a stallion asked our lab to perform a DNA test on a positive doping urine sample. The objective was to compare the urine DNA profile versus blood and hair DNA profiles from the same stallion. At first, 10 microsatellite markers were investigated to determine the horse identity. No results were obtained when horse specific markers were typed in the urine sample. In order to confirm the species origin of this sample we analyzed the mitochondrial cytochrome b gene. This analysis from blood and hair samples produced reproducible and clear PCR-RFLP patterns and DNA sequence match with those expected for horse, while the urine sample results were coincident with human. These results allowed us to exclude the urine sample from the questioned stallion and determine its human species origin, confirming the manipulation of urine sample.